Caregiving and caring with pride: Health behavior work among older gay married couples. Issue 1 (2nd January 2021) - Peak, Terry; Gast, Julie; Novak, Josh R.
Abstract: The focus of this qualitative study was to explore the perspectives of older gay married individuals around caregiving and health behavior work with their partners. The study used data from five long-partnered male couples who were recruited from a larger quantitative study of the health behaviors of gay married men and their partners. Thematic analysis identified three salient themes derived from the interview guide: (1) the health benefits of marriage, (2) what constitutes caregiving and health care work in marriage, and (3) the impact of caring for an ill or injured spouse on the marital relationship. Policy and practice implications for working with older gay married couples and LGBT couples generally are discussed.